Knowledge and attitudes toward clinical laboratory medicine among undergraduate medical interns in China: a cross-sectional survey - Yang, Yonggang; Tian, Jiyun; Chen, Baobing; Chen, Song (Frontiers in Medicine, 2025)
IntroductionUndergraduate clinical medical interns often lack systematic laboratory medicine training, potentially impacting their diagnostic reasoning and patient safety. This study aimed to assess the perceived knowledge and attitudes toward clinical laboratory medicine among this population in China, addressing a significant gap in medical education evaluation.MethodsA cross-sectional study was conducted from March to April 2025 across 11 general hospitals in Eastern China (Shanghai, Hangzhou, Nanjing, Suzhou, Ningbo, Xuzhou, Shaoxing, Yangzhou, Huzhou, and Taizhou). The self-developed and validated 13-item Clinical Laboratory Knowledge and Attitudes Questionnaire (CLKAQ) was structured in three domains: Knowledge, Attitudes and Suggestions. All 303 clinical interns completed the instrument. SPSS 25.0 and AMOS 26.0 were used. Descriptive statistics (frequencies/percentages for qualitative data; mean ± SD for quantitative data) summarized characteristics, knowledge, and attitudes. Scale reliability and validity were confirmed. Normality was assessed via Kolmogorov–Smirnov test. Group comparisons (gender, age, city tier) employed Mann–Whitney U and Kruskal-Wallis tests. Spearman correlation examined knowledge-attitude relationships. Multiple response and content analysis supplemented quantitative findings.ResultsThe mean self-perceived knowledge scale score (5-point Likert scale) among the 303 interns was 2.22 ± 0.424. The mean attitude scale score (5-point Likert scale) was 4.05 ± 0.312. Significant differences emerged in key competencies: Gender disparities in report interpretation (Q3), perceived importance of laboratory knowledge (Q5), and learning motivation (Q7); Age-group variations in perceived knowledge adequacy (Q1), (Q5) and (Q7); Interns from third-tier cities demonstrated consistently higher self-perceived competence across all knowledge and attitude dimensions than those in tier-1/2 cities (p < 0.05). A weak positive correlation linked knowledge and attitude levels (r = 0.171, p < 0.05). Critical differences were noted in preferred learning channels (Q10) and perceived barriers (Q11). Regarding open-ended questions, all interns expressed the need for increased clinical laboratory knowledge training and provided specific suggestions for such training.ConclusionUndergraduate clinical interns demonstrated suboptimal clinical laboratory knowledge but expressed highly positive attitudes toward learning. This underscores the critical need to enhance clinical laboratory training during clerkship. Implementing measures to improve knowledge is necessary. These findings inform curriculum optimization and educational strategy development for clinical continuing education.